Effect of Over-The-Counter (OTC) Drug Use Education on Community Knowledge Level in Karampuang Village, Panakkukang District, Makassar City through The Mother Active Learning Method - Nur Azizah, Rizqi; Rahmawati, Rahmawati; Wati, Aulia; Hardiyanti, Purnamasari; Rian Iryansyah, Rian Iryansyah (Journal of Pharmaceuticals and Natural Sciences, 2025)
Mother Active Learning (MAL) is an educational model of community empowerment to be more skilled in choosing drugs so that self-medication becomes more effective, safe, and cost-effective. This study aims to analyze the effect of over-the-counter (OTC) drug education on the public knowledge level in Panakukkang district through the MAL method. The research design used quasy-experimental, which is non-equivalent control group design. Sample was divided into control and treatment group consisting of 20 and 30 people. The data were analyzed descriptively by evaluating worksheets that were completed by participants. The analysis results found that the mean posttest value for the control group was 42.00 (SD=10.56), while the mean posttest value of treatment group was 84.67 (SD=10.74). Statistical tests found that there were significant differences between the mean values of both groups (p<0.01). Providing education to the community through the MAL method effectively increases knowledge related to the use of OTC drugs.